Muon-spin relaxation studies of the low-dimensional molecular compounds Mn(dca)(2)(pyz) and Fe(NCS)(2)(pyz)(2) - Lancaster, T; Blundell, S; Brooks, M; Pratt, F; Manson, J (2006)
We present the results of zero field muon-spin relaxation (mu+SR) studies of the molecular magnets Mn(dca)(2)(pyz) and Fe(NCS)(2)(pyz)(2) (where dca = [N(CN)(2)](-) and pyz = pyrazine). Both of these materials possess low-dimensional structural motifs resulting in magnetic behaviour consistent with this reduced dimensionality. Mn(dca)(2)(pyz) is formed from Mn-pyz-Mn chains, linked with dca anions to form two interpenetrating three-dimensional (3D) networks. Antiferromagnetic ordering in this compound is seen as a rapid change in the measured asymmetry around T-N = 2.5 K. Fe(NCS)(2)(pyz)(2) is a two-dimensional (2D) sheet-like polymer with the sheets consisting of Fe atoms bridged by pyz ligands. mu+SR measurements display both the 3D and 2D nature of the material in the measured relaxation spectra. We observe the transition into the LRO state below T-N along with an excitation of E = 1.09(5) meV above T-N associated with fluctuations within the correlated 2D layers. (c) 2005 Elsevier B.V. All rights reserved.